PSIKOEDUKASI BIJAK BERMEDIA SOSIAL UNTUK MENINGKATKAN RESPONSIBLE INTERNET USE DI DUNIA MAYA PADA SISWA SMUN 3 KEDIRI - Ardelia, Vania; Jaro'ah, Siti; Nur Widawati, Desi; Darmawanti, Ira; Nurchayati, Nurchayati (Universitas Negeri Surabaya, 2024)
The number of teenagers in Indonesia using social media has been increasing over time, along with the positive impact they have experienced. Through it, they can communicate interpersonally, in groups, and even as a business medium. However, negative impacts can arise if they are not cautious in using social media, such as addiction to social media, using devices not at the appropriate time and place, and cyber bullying. To prevent the negative impact of social media on adolescents, this community service activity aims to provide psychoeducation for SMU Negeri 3 Kediri students to be responsible in social media. The implementation of psychoeducation by providing material, questions and answers, along with a pre-test and post-test consisting of 5 questions about understanding digital literacy and the use of social media. The number of students who participated in psychoeducation activities was 68 students. The test results were analyzed by paired sample t-test using Jamovi software version 2.3.21 for Mac. The t-test results show that the average difference between the pre-test and post-test is very small, -0.147 and the significance value is 0.105. This indicates no significant change in the understanding of the wise use of social media before and after psychoeducation. This happens because students already have a pretty good knowledge about the use of social media.